On Being Homeless: Voices of Experience - Hansen, Noah; Nadelson, Louis S.; Hertzberg, Holly (International Journal on Homelessness)

(untitled) (Western Libraries, University of Western Ontario, 2026)
When addressing homelessness, often the last group to be included as participants in the process are those experiencing homelessness. Without understanding the perspective of those with lived experience and including them in the change process, it is unlikely that meaningful outcomes will be achieved. To better understand the inclusion and perspective of those with lived experience regarding community-based homelessness alleviation efforts, we conducted a phenomenological study focusing solely on those experiencing homelessness. The eight participants engaged in semi-structured interviews that revealed similarities and differences to extant research on efforts to address homelessness. Our results provide insight into how including lived experience may benefit community-based homelessness efforts.